Managing Chile's Macroeconomy during and after the Copper Price Boom - de Mello, Luiz (OECD Economics Department Working Papers, 2008)
Compliance with the structural budget surplus rule, which has been in place since 2001, has allowed the government to maintain a counter-cyclical fiscal stance in an environment of rising copper prices, while delivering a gradual reduction in public indebtedness. Monetary policy is conducted within a framework that combines inflation targeting with exchange-rate flexibility. A Fiscal Responsibility Law was promulgated in September 2006, strengthening the macroeconomic framework further by embedding the fiscal rule in law and setting out regulations for the use of fiscal savings. Complementary pension reform is being discussed in Congress with the objective of strengthening the pension system's solidarity pillar and encouraging retirement saving. The tax system is also being improved with a view to removing obstacles to financial deepening and to business-sector development. Government spending on social programmes is budgeted to rise considerably, in line with the authorities' emphasis on social development. The main challenge in the macroeconomic area is to maintain the policy setting that has served Chile so well over the recent copper-price upswing, while tempering demands for hiking public social spending and maintaining a lean public sector in a low-tax, low-debt environment. This paper relates to the 2007 Economic Survey of Chile (www.oecd.org/eco/surveys/chile)